Habituation of Asmaul Husna as a Strategy for Developing Students’ Religious Character: A Qualitative Study in a Rural Madrasah - Khairul Abdillah Harahap; Sukiman Sukiman; Nelly Setia Wati (Jurnal Pendidikan dan Pembelajaran Indonesia (JPPI), 2026)
This study aims to analyze the implementation process, students’ responses, and challenges of Asmaul Husna habituation as part of religious character development at MI Ma’arif Sambeng. This research employs a descriptive qualitative approach. Data were collected through participatory observation, semi-structured interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, supported by triangulation to ensure the validity of the findings. The results indicate that Asmaul Husnahabituation is carried out routinely every morning through several stages, including prayer, recitation, explanation of meanings, and motivational reinforcement. Most students demonstrate a positive level of enthusiasm in participating in the activity, although some remain passive and less focused during the process. The habituation contributes to the development of religious behaviors, such as improved discipline, the habit of greeting others, increased calmness during learning, and enhanced memorization of Asmaul Husna. However, the implementation still faces several challenges, including student boredom, weather conditions, limited learning media, and insufficient variation in teaching methods. These findings suggest that consistent religious habituation plays an important role in fostering students’ religious character and requires pedagogical innovation to enhance its effectiveness and meaningfulness.